Ergonomic investigation of a load carrying task during stair climbing - Kılınç, Ali. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Load carrying is one of the most frequent manual material handling task we encounter in daily life. The loads are carried either manually or by use of a material handling device. Manual carrying is performed by hands, shoulder, back or head. One of the most strenuous carrying tasks is the one involves carrying during stair climbing. Water bottle carrying on shoulder is a specific type of load carrying task during stair climbing widely performed in Turkey. This type of task may be extremely exhausting and risky leading to musculoskeletal pain and disorders of, especially, low back and shoulders. The main aim of this study was to estimate the workload induced by a 19 kg water bottle carrying task during stair climbing by three ergonomic approaches: biomechanical, physiological and psychophysical. Another aim was to determine the best one among the used three carrying methods. The task is performed by 20 young and healthy male participants with these methods: Carrying on shoulder (method 1), by stair climbing hand trolley (method 2) and by a home-built track type hand trolley (method 3). Biomechanical approach involved estimation of shoulder and low back forces and moments by hand calculation and also by use of UM-3DSSPP and also REBA risk estimation; physiological approach involved use of heart rate recordings; and psychophysical approach involved the use of Borg RPE scale (6-20) and also VAS (0-100). The results indicate that method 1 well-exceeds NIOSH safety limits of low back compressive force (4290±561 N for stoop and 4330±606 N for squat lifting). Method 2 and method 3, on the other hand, were safe (2078±467 N and 1740±362 N, respectively). L5/S1 shear forces and shoulder moments stay within safe limits for all the three methods. Physiologically, the task is a heavy task by all three methods. Psychophysically method 2 is the worst one and least preferred by the participants. In overall, track type hand trolley is better than other methods after considering all the approaches. In such low frequency jobs, the biomechanical criterion is the limiting factor; and thus the track type trolley should be used for such tasks.
Keywords: Human engineering.; Load factor design.